2017
DOI: 10.1002/mds.26947
|View full text |Cite
|
Sign up to set email alerts
|

Striatal activation by optogenetics induces dyskinesias in the 6‐hydroxydopamine rat model of Parkinson disease

Abstract: Selective optogenetic activation of the dorsolateral striatum elicits dyskinesias in the 6-hydroxydopamine rat model of PD. This effect was associated with a preferential activation of the direct striato-nigral pathway. These results potentially open new avenues in the understanding of mechanisms involved in l-dopa-induced dyskinesias. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
4
45
0
1
Order By: Relevance
“…Recently, the basic assumptions of Albin and colleagues have been tested experimentally in the mouse using cell type-specific optogenetic or chemogenetic stimulation methods. Overall, these studies have verified the notion that hyperactivity of iSPNs suppresses movement, whereas a large activation of dSPNs can elicit movement (Kravitz et al 2010) and also lead to dyskinesia (Perez et al 2017; Hernandez et al 2017; Alcacer et al 2017). Using different types of designer receptor exclusively activated by designer drugs (DREADD), Alcacer and colleagues have shown that the mode of dSPN activation is critical to the emergence of abnormal involuntary movements.…”
Section: The Striatummentioning
confidence: 61%
“…Recently, the basic assumptions of Albin and colleagues have been tested experimentally in the mouse using cell type-specific optogenetic or chemogenetic stimulation methods. Overall, these studies have verified the notion that hyperactivity of iSPNs suppresses movement, whereas a large activation of dSPNs can elicit movement (Kravitz et al 2010) and also lead to dyskinesia (Perez et al 2017; Hernandez et al 2017; Alcacer et al 2017). Using different types of designer receptor exclusively activated by designer drugs (DREADD), Alcacer and colleagues have shown that the mode of dSPN activation is critical to the emergence of abnormal involuntary movements.…”
Section: The Striatummentioning
confidence: 61%
“…Recent studies demonstrated that optical or chemogenetic stimulation of sensorimotor MSNs in parkinsonian animals can evoke dyskinesia (Alcacer et al, 2017; Hernández et al, 2017; Perez et al, 2017); dyskinesias have also been reported with dMSN stimulation in healthy animals (Rothwell et al, 2015). These observations suggest synchronous activation of many dMSNs in the sensorimotor striatum may be sufficient to cause dyskinesia but do not indicate which neurons are normally engaged in LID.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the study of Perez and colleagues suggests that the selective activation of direct pathway MSNs is sufficient to induce dyskinesia, Hernández and colleagues demonstrate that concomitant activation of direct and indirect pathways is equally able to induce optodyskinesias, suggesting that activation of the indirect pathway does not seem to counteract this effect.…”
mentioning
confidence: 96%
“…In this issue of Movement Disorders, two interesting studies report the results of in vivo optogenetic approaches in rodents, to address the mechanisms underlying the induction of dyskinesia . In the first study, Hernández and colleagues have used optogenetic stimulation of the striatum to induce dyskinesias in a hemiparkinsonian model of PD in rats .…”
mentioning
confidence: 99%